The Study Of Theological Sin And The Meaning Of Transformation Based On Romans 12:1-2 - Tony Andrean; David Ming (Theological Journal Kerugma, 2020)
"In the beginning He created the heavens and the earth, the earth was formless and empty; pitch darkness covered the great oceans, and the Spirit of God drifted over the surface of the earth '(Genesis 1: 1). chaotic "or" irregular. "(Warren Baker, Study OId Testament. AMG publisher, 1994: 2-3G.). Then in the process of creating humans for maintain the universe, but man falls into sin so that his mind or intellect is dominated by sin. What is produced by the mind ruled by sin? The Scriptures state the following: first, the human character is in vain (Romans 1:21). Second, it is not fair for anyone to be wise (Romans 3.11). Third, the human mind becomes evil (Ephesians 5: 4, the human mind is hostile to God and results in evil deeds 1.21) In further development, the universe is not getting better, it's actually getting more and more damaged. Natural disasters occur everywhere, economic conditions are chaotic, laws are violated by the leaders themselves, society is socially hostile to each other, crime is everywhere. With the chaotic event, humans crave a real change and share of activities carried out to realize these desires, among others, with the current plasticity, the transformation movement. The author conducted this research and the results are expected to provide information and additional insight for parties related to the problem of understanding the doctrine of existence and the meaning of sin, thus understanding the meaning of transformation based on the Bible to be changed to not sin anymore. The expected benefit is to provide correct knowledge to the congregation and God's servants regarding the effects of sin in their lives. Especially in service, how they anticipate sin and experience transformation changes in their lives. Thus it can remind every believer to remain faithful and abstain from every action that brings sin